Effect of Metal Collar on Marginal Distortion of Base Metal Crowns - Grami Panah F; Fazel A; Haj- Mahmoodi M (Tehran University of Medical Sciences, 2000)
It has been shown that noble alloys require metal collar to resist distortion when subjected to"nrepeat firing cycle of porcelain. Metal collar is undesirable due to esthetic concerns. Since base metal"nalloys have superior physical properties, it seems that metal collar would not be necessary for obtaining"nbetter marginal adaptation of base metal crowns. The Purpose of this study was to evaluate the effect of"nmetal collar on marginal distortion of base metal- ceramic crowns, Twenty base metal copings were"nconstructed and divided into two groups with and without collars. After surface preparation, porcelain"nwas applied onto the surface of specimens. Marginal gap was measured by scanning electron microscope"nduring three stages of crown fabrication: before degassing, after degassing and after glazing. The mean"nmeasurements in collarless group were; 21.4±13.4, 2I.4±14.9 and 21.9±11.9 u_m, respectively, and in-"ngroup with collar; 24.7±11.4, 24.0±! 1.5 and 26.6±11.7 urn, respectively. Two- way ANOVA revealed"nno significant difference in the mean values between two groups and among different stages of crown"nfabrication. The results of this study showed that base metal alloys did not distort during crown"nfabrication and metal collar had no effect on the amount of marginal opening (gap).